2016
DOI: 10.1016/j.lssr.2015.12.001
|View full text |Cite
|
Sign up to set email alerts
|

A priming dose of protons alters the early cardiac cellular and molecular response to 56 Fe irradiation

Abstract: Purpose Recent evidence suggests that the heart may be injured by ionizing radiation at lower doses than was previously thought. This raises concerns about the cardiovascular risks from exposure to radiation during space travel. Since space travel is associated with exposure to both protons from solar particle events and heavy ions from galactic cosmic rays, we here examined the effects of a “priming” dose of protons on the cardiac cellular and molecular response to a “challenge” dose of 56Fe in a mouse model.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 32 publications
2
28
0
1
Order By: Relevance
“…The acute dose of 56 Fe was selected to reflect the estimated cumulative dose to which astronauts could be potentially exposed during deep space exploration due to the galactic cosmic rays and is the lowest dose previously shown to cause cell loss in in vivo settings during deep space exploration due to the galactic cosmic rays (Rola et al, 2008). Sequential irradiation with protons before iron ions reflects the likely exposure of cells in the space environment where daily traversals by protons are accompanied by infrequent traversals by heavy ions (Ramadan et al, 2016). At the selected energy of 600 MeV/n, thorough penetration of the animals with a relatively flat Bragg peak entrance region is expected.…”
Section: Methodsmentioning
confidence: 99%
“…The acute dose of 56 Fe was selected to reflect the estimated cumulative dose to which astronauts could be potentially exposed during deep space exploration due to the galactic cosmic rays and is the lowest dose previously shown to cause cell loss in in vivo settings during deep space exploration due to the galactic cosmic rays (Rola et al, 2008). Sequential irradiation with protons before iron ions reflects the likely exposure of cells in the space environment where daily traversals by protons are accompanied by infrequent traversals by heavy ions (Ramadan et al, 2016). At the selected energy of 600 MeV/n, thorough penetration of the animals with a relatively flat Bragg peak entrance region is expected.…”
Section: Methodsmentioning
confidence: 99%
“…However, when administered 24 hours before a subsequent exposure to iron ions (0.5 Gy, 600 MeV/n), proton exposure prevented iron ion-induced markers of inflammatory infiltration, cardiac remodeling, and formation of cleaved caspase 3 [108]. These results suggest that proton exposure induced an as of yet unknown response in the heart that provided protection against further charged particle exposure.…”
Section: Cardiovascular Effects Of Space Radiationmentioning
confidence: 99%
“…More recent murine studies have shown similar effects of sequential irradiation with protons followed by HZE ions in the lung, heart and hippocampus. 2729 Collectively, these studies suggest that exposure of human cells, notably hematopoietic stem cells (HSC), to SEP and GCR radiation may significantly increase risk of carcinogenesis, and highlights the need for additional research on human cells using combinations of radiation species (ions) and exposure schemes that best approximate the space radiation environment.…”
Section: Introductionmentioning
confidence: 99%